The incidence and predictors of peripheral arterial disease among type 2 diabetes mellitus patients at Felege Hiwot Comprehensive Specialized Hospital, Northwest Ethiopia, 2023: A retrospective follow-up study. - Dessalew Abelneh Woleli; Gebiyaw Wudie Tsegaye; Taye Abuhay; Abyot Terefe Teshome; Gebrie Getu Alemu (PLoS ONE)
Background Peripheral arterial disease is a blockage or narrowing of arteries transporting blood from the heart to the legs and feet. Type 2 diabetes mellitus is the second most common risk factor for peripheral arterial disease. This condition is associated with patient mortality and morbidity. However, there is limited evidence on the time to develop peripheral arterial disease, its incidence, and its predictors in the Amhara region, Ethiopia. Objective To assess the incidence and predictors of peripheral arterial disease among adult type 2 diabetes mellitus patients at Felege Hiwot Comprehensive Specialized Hospital, Northwest Ethiopia, 2023. Methods A retrospective follow-up study was conducted using data from 552 type 2 diabetes mellitus patients, selected by simple random sampling from January 2006 to December 2021. Data from patient charts and follow-up forms were extracted using a standardized tool, entered into Epi-Data version 3.1, and analyzed in STATA version 14. Kaplan-Meier curves, life table, and Cox regression model were used to assess survival times, survival probabilities, and identify independent predictors of peripheral arterial disease, respectively. Results The final analysis included 552 records. The median time for peripheral arterial disease was 13.5 years (95% CI: 11, 14.5). Being female (Adjusted Hazard Ratio (AHR) =  2.18, 95% CI: 1.36, 3.51), age above 65 years (AHR =  1.66, 95% CI: 1.06, 2.61), and fasting blood sugar of over 140 mg/dl (AHR =  3.34, 95% CI: 1.62, 6.90) were predictors for time to peripheral arterial disease in type 2 diabetes mellitus patients. We observed an incidence rate of 29 cases of peripheral arterial disease per 1000 person-years of observation (95% CI: 24-36). Conclusion and recommendation Most peripheral arterial disease occurs after 10 years of diagnosis of type 2 diabetes mellitus. The incidence rate of peripheral arterial disease was high. Female sex, older age, and elevated baseline fasting blood sugar predicted the time until peripheral arterial disease developed. Therefore, clinicians and other stakeholders shall emphasize those types of type 2 diabetes mellitus patients who are female, older age, and with raised fasting blood sugar.